Dampak Latihan Bayangan Dalam Kemampuan Teknik Pukulan Push Forehand Dalam Permainan Tenis Meja - Ahmad Pratama, Sandi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. To improve the abilities of atlets, a trainer is required to guide atlets in efforts to help and spur development in achieving learning outcomes. For this reason, a trainer must be able to choose and determine the appropriate training method or technique. Materials and methods. The research design used One Group Pretest-Posttest Design. The research subjects used were 26 people with purposive sampling technique. Results. The results of data analysis using the test obtained the t-value of 7.710 and the t-table of 2.060. Conclusions. So that from the results of this study it can be concluded that there is an effect of shadow training on the Improvement of the Forehand Push Technique in Table Tennis.